Arsenic accumulation in Pteris vittata: Time course, distribution, and arsenic-related gene expression in fronds and whole plantlets. (15th September 2022) - Antenozio, Maria Luisa; Capobianco, Giuseppe; Costantino, Paolo; Vamerali, Teofilo; Bonifazi, Giuseppe; Serranti, Silvia; Brunetti, Patrizia; Cardarelli, Maura
Abstract: In this work, arsenic (As) accumulation and distribution over time in Pteris vittata young fronds from adult plants and in whole plantlets, grown on a highly contaminated As-soil, was determined by μ-XRF. A linear increase in As content up to 60 days was found in young fronds at different times, and a progressive distribution from the apex to the base of the fronds was observed. In whole plantlets, As signal was detectable from 9 to 20 days in the apex of a few fronds and fiddleheads. Later, up to 60 days, As was localized in all fronds, in the rhizome and in basal part of the roots. The dynamics of expression of As-related genes revealed a good correlation between As content and the level of the As (III)-antiporter PvACR3 transcript in plantlets roots and fronds and in young fronds. Moreover, the transcription of As (V)-related gametophytic genes PvGAPC1, PvOCT4 increases over time during As accumulation while PvGSTF1 is expressed only in roots. Here, we demonstrate the suitability of the μ-XRF technique to monitor As accumulation, which allowed us to propose that As is initially directly transported to fiddleheads and apex of fronds, is later distributed to the whole fronds and simultaneously accumulated in the rhizome and roots. We also provide indications on the expression of candidate genes possibly involved in As (hyper)accumulation. Graphical abstract: Image 1 Highlights: By means of μ-XRF we established the accumulation of As in plantlets and young fronds of P. vittata. We provide new evidence on the distribution of As in the different organs of whole plantlets over time. We evaluated the expression in fern organs of genes involved in As accumulation.